Conceptual problems of financial accounting in a digital economy - N. K. Rozhkova; U. Yu. Blinova (Управление)
The article shows modern problems of financial accounting associated with formation of conceptual accounting provisions in the context of digitalisation of society and economy. An open system of financial accounting, consisting of interrelated and interdependent elements, functions in the new economic conditions. The accounting concept created by regulatory legal acts does not meet the requirements of practice and does not meet current users’ needs. There are prerequisites for changing the entire accounting system due to modern technologies (blockchain, artificial intelligence), which can completely change the traditional ideas about the formation of accounting and analytical information as well as main functions of accountant. The study of the current financial accounting concept and the formulation of directions for its development in the digital economy formation conditions based on the identification of conceptual problems of the modern accounting system characteristic is the purpose of the work. An analysis of the digital economy impact on the accounting system formation, a review of the main system elements that are undergoing the greatest transformation and the identification of problem areas that need to be addressed in the formation of the digital economy are the objectives of the study. The most relevant problem is the legal regulation of financial accounting, as well as issues of methodological nature related to the need for internal content, proposed by the authors of the accounting system in accordance with the changed digital economy information needs.